# Solve the linear equation: (3t - 2)/4 - (2t + 3)/3 = 2/3 - t

**Solution:**

(3t - 2)/4 - (2t + 3)/3 = 2/3 - t

Multiply both sides by the LCM of the denominators to get rid of fractional denominator.

Now transpose variables to one side and constants to another side to form a linear equation.

(3t - 2)/4 - (2t + 3)/3 = 2/3 - t

LCM of the denominators is 12

Multiply the LCM on both sides

⇒ 12[(3t - 2)/4 - (2t + 3)/3] = 12[2/3 - t]

⇒ 9t - 6 - 8t - 12 = 8 - 12t

⇒ 13t = 26

Hence,

t = 26/13 = 2

**Video Solution:**

## Solve the linear equation: (3t - 2)/4 - (2t + 3)/3 = 2/3 - t

### NCERT Solutions Class 8 Maths - Chapter 2 Exercise 2.5 Question 5

**Summary:**

The solution to the given linear equation (3t - 2)/4 - (2t + 3)/3 = 2/3 - t is t = 2